Deteksi Hunian Di Tempat Parkir (Occupancy Detection In Parking Lot) - Echa Oktamiani Maulana (STIKes Ibnu Sina Ajibarang, 2024)
MSIB (Certified Independent Study and Internship) is one of the activity programs at the Merdeka Campus which aims to help students improve their skills and develop themselves. MSIB appointed Orbit Future Academy as one of the partners in the Independent Study program. Founded in 2016 with the aim of improving the quality of life through innovation, education and skills training. In accordance with its mission, namely